Mentoring Matters: Racial Ethnic Minority Undergraduates' Cultural Fit, Mentorship, and College and Life Satisfaction. Issue 2 (5th July 2016) - Castellanos, Jeanett; Gloria, Alberta M.; Besson, Doriane; Harvey, Le Ondra Clark
Abstract : This study examined the degree to which cultural fit (cultural congruity in combination with perception of the university environment) and the dimensional noncognitive processes of mentoring predicted college satisfaction and life satisfaction for 238 racial and ethnic minority undergraduates from two university contexts. Group differences as well as differences in strength of relationships emerged by site and mentor status. Perception of the university environment was the strongest positive predictor of college satisfaction, whereas cultural congruity was the strongest predictor of life satisfaction. Limitations, future research directions, and implications of the study's findings are discussed.